2010
DOI: 10.1038/cgt.2010.30
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect antitumor effects by human peripheral blood lymphocytes expressing both chimeric immune receptor and interleukin-2 in ovarian cancer xenograft model

Abstract: Human peripheral blood lymphocytes (PBLs) electroporated with RNA encoding anti-Her-2/neu-specific chimeric immune receptor (CIR) have been reported to elicit potent immune responses against SKOV3 tumors in a nude mouse model. However, CIRelectroporated PBL (CIR-PBL) did not proliferate, and the cell number rapidly decreased in the absence of exogenous interleukin-2 (IL-2). In this study, PBLs electroporated with both CIR and IL-2 RNA (CIR/IL-2-PBL) were studied to determine whether antitumor effects could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…At 35 months median follow-up survival was potentially better than historical controls, suggesting possible efficacy, which was corroborated by a longer-term survival analysis in 2000 [49]. More recent trials of intraperitoneal 90 yttrium-labeled HMFG1 suggest that, whereas it can control local (intraperitoneal) disease, distant relapses could offset any overall survival benefits. Nonetheless, the potential to control intraperitoneal disease could be exploited further [27].…”
Section: Anti-milk Fat Globulin-1mentioning
confidence: 83%
See 3 more Smart Citations
“…At 35 months median follow-up survival was potentially better than historical controls, suggesting possible efficacy, which was corroborated by a longer-term survival analysis in 2000 [49]. More recent trials of intraperitoneal 90 yttrium-labeled HMFG1 suggest that, whereas it can control local (intraperitoneal) disease, distant relapses could offset any overall survival benefits. Nonetheless, the potential to control intraperitoneal disease could be exploited further [27].…”
Section: Anti-milk Fat Globulin-1mentioning
confidence: 83%
“…Follow-up studies testing additional antibodies continued to establish the relative safety of this approach and continued to identify occasional long-term clinical responses [46]. A phase II trial using 90 yttrium-labeled HMFG1 failed to demonstrate significant clinical benefits in 25 patients, and dose-escalation was eventually limited by myelosuppression [47].…”
Section: Anti-milk Fat Globulin-1mentioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly, the mRNA‐transfected T cells show antigen‐specific effector functions including secretion of cytokines and selective lysis of antigen‐expressing target cells. Furthermore, potent antitumor responses have been reported in animal models for leukemia, mesothelioma, and ovarian cancer . Accordingly, a first phase I clinical trial for the treatment of patients with malignant pleural mesothelioma has been reported .…”
Section: Therapeutic Uses Of Mrnamentioning
confidence: 99%